Prevalence of oral lesions in relation to habits : Cross-sectional study in South India. - Saraswathi T; Ranganathan K; Shanmugam S; Sowmya R; Narasimhan Prem; Gunaseelan R (Wolters Kluwer Medknow Publications, 2006)
BACKGROUND: Smoking, drinking and chewing tobacco product, common habits in India have been positively associated with oral lesions. No study has been conducted in this part of Tamilnadu regarding the prevalence of oral lesions in relation to habits. METHODS: A hospital based cross-sectional study was carried out at Ragas Dental College, Chennai. Already existing data of two thousand and seventeen consecutive patients from sub-urban areas of Chennai, who attended the outpatient department, at Ragas Dental College, for dental complaints during a period of three months in 2004, who underwent oral examination and interviewer based questionnaire was used. RESULTS: Oral soft tissue lesions were found in 4.1% of the study subjects. The prevalence of leukoplakia, OSF and oral lichen planus was 0.59%, 0.55%, and 0.15% respectively. The prevalence of smoking, drinking alcoholic beverages and chewing was 15.02%, 8.78% and 6.99% respectively. Smoking and chewing were significant predictors of leukoplakia in this population. DISCUSSION: The prevalence of leukoplakia, OSF and oral lichen planus in our study population is similar to those found in other populations. The prevalence of consumption of alcoholic beverages in our study population was higher when compared to the Indian National Sample Survey study. However the prevalence of smoking and chewing was found to be lower. Smokers were more likely to develop smoker′s melanosis compared to other lesions. Among those who consumed alcoholic beverages alone, the prevalence of leukoplakia was higher compared to other lesions. OSF was the most prevalent lesion among those who chewed panmasala or gutkha or betel quid with or without tobacco.